Pemberdayaan Desa Takerharjo via Pertanian Berkelanjutan dan Edukasi Kesehatan - Nasihin, Muh Nur Ali Khoirun; Feryani, Dwin; Dwiyanti, Dias; Azahrotussholikha, Nahdhiya; Sundari, Ariefah; Syaikudin, Ahmad Yani; Rozi, Ahmad Fathur (Penerbit Goodwood, 2025)
Purpose: This community service initiative aims to empower the residents of Takerharjo Village by introducing sustainable agricultural practices and providing health education. The goal is to improve local welfare, enhance food security, and promote community health through innovative and practical solutions. Methodology/approach: The program was conducted in Takerharjo Village, involving 50 farmers and 30 households. Sustainable agricultural tools such as organic fertilizers, drip irrigation systems, and pest control traps were introduced. Health education sessions were held using interactive methods, including workshops and demonstrations. Surveys and interviews were conducted to assess the community's needs and evaluate the program's impact. Data were analyzed using Microsoft Excel for quantitative results and thematic analysis for qualitative feedback. Results/findings: The initiative successfully increased agricultural productivity by 25% through the adoption of sustainable practices. Health education improved community awareness of hygiene and nutrition, leading to healthier lifestyles. Participants reported higher satisfaction and confidence in managing their farms and health. Conclusion: The community service program in Takerharjo Village demonstrated that sustainable agricultural innovation and health education can enhance productivity, community participation, and environmental health. Multi-stakeholder collaboration and technology integrated with local wisdom were key to achieving sustainable village transformation. Limitations: The study was limited by the short duration of the program and the small sample size, which may affect the generalizability of the results. Contribution: This study contributes to the fields of community development, sustainable agriculture, and public health. It provides a model for other rural communities to adopt similar practices, fostering local progress and well-being.